Empowerment of Housewives in Producing WasteBased Creativity Around the House During Covid- 19 PPKM - Samlan Ahmad; Dina Rahmawati; Sukardi Abbas (Archipelago, 2021)
Garbage that is not managed properly can cause the environment to become dirty and cause river siltation that results in flooding. The amount of waste production is in line with the number of population, the higher the rate of population growth, the greater the rate of waste production. Waste management can not only be done downstream, but also start from upstream. Many programs have been carried out in waste management, one of which is the procurement of waste banks. The waste bank program encourages the public to sort before depositing inorganic waste in garbage banks. Inorganic recyclable waste, such as plastic bottles of used mineral water can be economically valuable by means of being in tubes on garbage banks, while organic waste such as leftover vegetables and fruit can be further processed into eco-enzymes. This activity aims to transfer knowledge and technology of processing organic waste into ecoenzymes, so that the community can participate in maintaining the sustainability of the earth. The methods of activities carried out are extension and demostration. This activity can achieve the goals in accordance with the objectives, this can be seen from the participation and enthusiasm of the community during the activity.Keywords: Producing Waste based Creativity, PPKM Covid-19